Science and Arts at the University of Maribor - Korošak, Dean; Nekrep, Andreja; Vukman, Joso; Knez, Željko; Pahor, Dušica; Stožer, Andraž; Tominc, Polona; Bajc, Gorazd; Rimele, Oto; Svete, Tomaž (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2025)
Throughout its history, the University of Maribor has built a strong research and artistic tradition, combining the originality of scientific thought and creative expression with social responsibility. Despite comparatively limited financial resources, it demonstrates high scientific efficiency and competitive research quality, reflected in publications with high scientific impact. Scientific research activities are strategically implemented through three programme cores: Artificial Intelligence and Data Science in Biomedicine, Materials and Technologies as well as Heritage Science and Climate Change. Emphasis is placed on horizontal integration and the creation of interdisciplinary synergies. Development takes place in the fields of natural sciences and engineering, life sciences, social sciences and humanities, and artistic creation. A key role is played by state-of-the-art research infrastructure, in which the University continuously invests. The University of Maribor actively develops the principles of open science, strengthens international connectivity, respects ethics in research, and involves students in research work to address social challenges and support the economic progress of the region.